"Double syringe!": Using a popular TV show argument to illustrate the differences of objective and interpretive paradigmatic perspectives in action. Issue 3 (2nd July 2020) - Sánchez Sánchez, Virginia; Martinez, Emilly K.; Jackson, Diane L.
Abstract : Metatheoretical perspectives, and their role in influencing the research process, can be difficult for undergraduate students to grasp. The communication field brings together myriad approaches to communication, lending to students' confusion (Muller, H. L., & Craig, R. T. [2007]. Introduction. In R. T. Craig & H. L. Muller [Eds.], Theorizing communication: Readings across traditions [pp. ix–xviii]. Thousand Oaks, CA: Sage). To understand theory building, students must grasp how paradigmatic assumptions inform approaches to research (e.g. the questions asked, methodology, and analysis). To simplify these concepts, Griffin et al. (Griffin, E., Ledbetter, A., & Sparks, G. [2018]. A first look at communication theory [10th ed.]. New York, NY: McGraw-Hill) place theories on a continuum, ranging from interpretive (e.g. constructionist) to objective (e.g. positivist, post-positivist). These simplified terms lose the nuances of each paradigm but allow students to become familiar with how differences in world views shape scholars' approaches to the study of communication. The purpose of this activity is to provide students with an opportunity to further their understanding about how metatheoretical assumptions influence approaches to research. Courses: Introduction to Communication Theory, Introduction to Communication, Introduction to Research Methods. Objectives: Describe the metatheoretical assumptions held by "objective" and "interpretive" scholars Distinguish among paradigmatic approaches Explain how metatheoretical assumptions influence scholars' approaches to research.